2016
DOI: 10.1120/jacmp.v17i5.6320
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric validation for an automatic brain metastases planning software using single‐isocenter dynamic conformal arcs

Abstract: An automatic brain‐metastases planning (ABMP) software has been installed in our institution. It is dedicated for treating multiple brain metastases with radiosurgery on linear accelerators (linacs) using a single‐setup isocenter with noncoplanar dynamic conformal arcs. This study is to validate the calculated absolute dose and dose distribution of ABMP. Three types of measurements were performed to validate the planning software: 1, dual micro ion chambers were used with an acrylic phantom to measure the abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…With the recent introduction of commercial single‐isocenter planning algorithms for simultaneously treating multiple brain metastases, either using automated dynamic conformal arcs or automated VMAT, more dosimetric comparison to GK is required. These studies have already demonstrated a reduction in monitor units compared with conventional VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent introduction of commercial single‐isocenter planning algorithms for simultaneously treating multiple brain metastases, either using automated dynamic conformal arcs or automated VMAT, more dosimetric comparison to GK is required. These studies have already demonstrated a reduction in monitor units compared with conventional VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…This hollow phantom can be printed with bone‐mimicking materials based on anatomical structures of a past patient, based on CT data or scans, and it is filled with water and a 3D polymer gel dosimeter insert to simulate soft tissue equivalence 30 . Irradiation of this gel phantom provides the ability to evaluate 3D dose distributions for SRS 18,31,32 . The custom phantom is designed with a glossy white exterior, which is incompatible with the SGRT cameras.…”
Section: Methodsmentioning
confidence: 99%
“…30 Irradiation of this gel phantom provides the ability to evaluate 3D dose distributions for SRS. 18,31,32 The custom phantom is designed with a glossy white exterior, which is incompatible with the SGRT cameras. A nude makeup foundation (Stay Matte, Rimmel, London) was applied to the phantom's surface to simulate a skin tone visualizable by the scanner units.…”
Section: Rtsafe Prime Phantommentioning
confidence: 99%
See 1 more Smart Citation
“…3D printing is being increasingly employed in radiotherapy for applications ranging from construction of treatment accessories (Canters et al 2016, Lindegaard et al 2016, Ricotti et al 2016, Jones et al 2017, Zhao et al 2017 to patient geometry and/or material reproduction (Ehler et al 2014, Liu et al 2016, Madamesila et al 2016, Kamomae et al 2017, Yea et al 2017. Regarding the latter, introducing material inhomogeneities in the phantoms has recently drawn considerable attention.…”
Section: Introductionmentioning
confidence: 99%